2021
DOI: 10.1111/add.15523
|View full text |Cite
|
Sign up to set email alerts
|

A new generation of transdermal alcohol biosensing technology: practical applications, machine ‐learning analytics and questions for future research

Abstract: The use of transdermal alcohol monitors has burgeoned in recent years, now encompassing hundreds of thousands of individuals globally. A new generation of sensors promises to expand the range of applications for transdermal technology exponentially, and advances in machine‐learning modeling approaches offer new methods for translating the data produced by transdermal devices. This article provides (1) a review of transdermal sensor research conducted to date, including an analysis of methodological features of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 59 publications
(111 reference statements)
0
27
0
Order By: Relevance
“…Further refinement to the Skyn device could troubleshoot this wide variation of TAC thresholds, so that future studies can develop robust rules that can convert Skyn TAC data to automated detection of drinking versus non-drinking. In addition, we demonstrated that the Skyn's high sampling frequency was robust to field conditions, which could be leveraged for more sophisticated analyses, such as TAC change over time after resolving fluctuation issues (Appendix S2) or machine-learning upon the rich time-series features (Fairbairn & Bosch, 2021;Fairbairn et al, 2020).…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further refinement to the Skyn device could troubleshoot this wide variation of TAC thresholds, so that future studies can develop robust rules that can convert Skyn TAC data to automated detection of drinking versus non-drinking. In addition, we demonstrated that the Skyn's high sampling frequency was robust to field conditions, which could be leveraged for more sophisticated analyses, such as TAC change over time after resolving fluctuation issues (Appendix S2) or machine-learning upon the rich time-series features (Fairbairn & Bosch, 2021;Fairbairn et al, 2020).…”
Section: Main Findingsmentioning
confidence: 99%
“…Through recent advances in alcohol biosensor technology, a new generation of TAC sensors have emerged with the potential to expand the opportunities for real-time, objective monitoring of alcohol consumption. Among these new sensors, the most promising is the Skyn by BACTrack (San Francisco, CA) (Davis-Martin et al, 2021;Fairbairn & Bosch, 2021;Wang et al, 2019). Compared to the SCRAM CAM, the Skyn is wrist-worn, less invasive (Wang, et al, 2019(Wang, et al, , 2021, samples alcohol exposure more frequently, releases data immediately by Bluetooth, and detects drinking with less time delay (Fairbairn & Kang, 2019;Fairbairn et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Wrist-worn devices have ranged from early sensors such as Giner WriSTAS (Giner Inc., Newton, MA, USA; resembling a wrist watch, now discontinued [33,34,48]) to newgeneration devices such as the BACtrack Skyn (from BACtrack/KHN Solutions Inc., San Francisco, CA, USA; see Fig. 1b [16,21,23,49]), featuring smartphone connectivity and sleek, fitbit-like designs [14,16,23,46]. Wrist-and arm-worn devices have traditionally employed sensors that rely on passive (rather than active pump-generated) airflow across the sensor, which has diminished demands on battery life and so permitted faster sampling speeds.…”
Section: Transdermal Sensor Types and Factors Impacting Transdermal A...mentioning
confidence: 99%
“…Thus, transdermal sensors have the potential to assess drinking continuously, passively and unobtrusively by measuring the concentration of alcohol in sweat and insensible perspiration. In addition to their existing application as abstinence monitors in the criminal justice system [12,13], a range of additional uses have been proposed for transdermal sensors, including as relapse-detecting monitors capable of prompting 'just-in-time' addiction intervention [14,15], as drinking risk-level indicators to inform the advisability of driving [14,16,17] and as continuous trackers capable of unobtrusively assessing drinking during the course of months and even years for implementation in research studies [5,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation